Reviews - Katie Kane; Sheryl Mylan; Jerome Bump (Journal of the Assembly for Expanded Perspectives on Learning, 1998)
Reviews Katie Kane. Women Writing Culture. (Gary A. Olson and Elizabeth Hirsh, Eds., 1995). Women/ Writing/ Teaching. (Jan Zlotnik Schmidt, Ed., 1998). Sheryl Mylan. ARTiculating: Teaching Writing in a Visual World. (Pamela B. Childers, Eric Hobson, and Joan A. Mullin, 1998). Jerome Bump. Emotional Intelligence. (Daniel Goleman, 1995).